Assessment of Upper Basic Students' Knowledge in Some Social Studies' Basic Education Curriculum Contents in ondo West Local Government Area of Ondo State (Global Journal of Human-Social Science, 2023)
This study assessed the knowledge of upper basic social studies students in some selected social studies contents. Specifically, the study investigated the knowledge acquisition of upper basic two students in some junior secondary one (JS I) social studies curriculum contents. 453 upper basic two social studies students from five randomly selected secondary schools were involved in the study. Six JS I social studies curriculum contents were selected and assessed in the study. The contents are: family life; culture; meaning and history of social studies; examination ethical concepts; HIV/AIDS and drug abuse. An instrument titled Knowledge Assessment in Social Studies Contents (KASSC) was used to generate data for the study. Descriptive analysis was used to analyze data obtained from the study.
Keywords: assessment; students’ knowledge; family life; examination ethical concepts; drug abuse